Proceedings of the 12th European Agent Systems Summer School Student Session - Tina Balke; Reda Yaich (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2010)
This volume contains the papers presented at the Student Session of the 12th European Agent Systems Summer School (EASSS) held on 25th of August 2010 at Ecole Nationale Superieure des Mines de Saint-Etienne, France. The Student Session, organised by students, is designed to encourage student interaction and feedback from the tutors. By providing the students with a conference-like setup, both in the presentation and in the review process, students have the opportunity to prepare their own submission, go through the selection process and present their work to each other and their interests to their fellow students as well as internationally leading experts in the agent field,both from the theoretical and the practical sector. Table of Contents: Andreea Urzica, Distributed Reputation Extraction in Multi-Agent Systems ... 5; Andrea Santi, From Objects to Agents: Rebooting Agent-Oriented Programming for Software Development . . . 12; Christopher J. Garthe, Understanding ecological impacts of recreation through modeling of spatial visitor behavior . . . 20; Muntasir J. Al-Asfoor, A Study of Resource Discovery in Open Multi Agent System and Grid Environment . . . 25.
urn:nbn:de:bvb:703-opus-7323
Keywords: 330; Autonomer Agent; Agent; Künstliche Intelligenz